Informal and illegal mining and mercury pollution in Madre de Dios: A public health problema - Osores Plenge, Fernando (2012)
Alluvial gold mining, which takes place informally or illegally within the mining allowed areas and within the forbidden areas for mining in Madre de Dios, generates a direct and indirect impact upon people's health, not only of miners who work in high risk conditions, exposing themselves to dust, excessive solar radiation, high humidity, noise, vibrating mechanical trauma, mercury which may be inhaled or accidentally ingested, particularly in areas where gold is sold and bought; and also it implies exposure to toxic chemicals and working accidents. On the other hand, the general population is exposed to water pollution because of mercury waste thrown to water sources used by people living in Madre de Dios river basin, and other problems include Amazonian forest and soil destruction, massive migration leading to an increase in transmissible diseases, social violence, person trafficking, prostitution, and unhealthy food.